Korelasi antara Kebiasaan Merokok dan Nilai Arus Puncak Ekspirasi (APE) pada Mahasiswa yang Tinggal di Rumah Susun Mahasiswa Universitas Tanjungpura - ., Kurnia Kumala Putri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Smoking is a bad habit and is injurious to health. Various organ systems in the body can be exposed to the ill effects of smoking, the most frequent is respiratory system. Smoking can lead to occurrence of narrowing and obstruction of the airway and cause a decrease in lung function. Objective: The purpose of this research is to know the relationship between smoking habit and PEFR values on students living in Rumah Susun Mahasiswa Universitas Tanjungpura (RUSUNAWA UNTAN). Methods: This research is an observational analytic study with cross sectional research design. Samples were taken from all students who live in RUSUNAWA UNTAN in October 2013 with consecutive sampling method. Data were analyzed by point biserial test. Result: One hundred and three subjects were included in this research. Thirty nine subjects (37,9%) have smoking habit. The mean of PEFR value in overall subjects is 498,83 liters/minute. The result of corelational analysis between smoking habit and PEFR value is r=-0,481 . Conclusion: There was a moderate correlation between pefr values and smoking habit, where the smoker students show lower pefr values than non-smoker students. Keyword : Peak Expiratory Flow Rate, Peak Flow Meter, Cigarette, University Student, Pulmonary Function 1)          Medical school, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan. 2)          Functional medical unit of pulmonary disease, Regional General Hospital dr. Soedarso, Pontianak, West Kalimantan. Department of physiology, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan